Corporate Social Responsibility And Earnings Management: Insights From Sri Lanka - Muraleetharan, P.; Sinthuja, N. (Faculty of Management Studies and Commerce, University of Jaffna, Sri Lanka, 2025)
This study examines the impact of Corporate Social Responsibility (CSR) on earnings management among listed companies in Sri Lanka. CSR practices have been significant, with organisations engaging in CSR initiatives to meet stakeholder expectations. However, this may lead to earnings manipulation to align financial reporting with these expectations. The research examines the relationship between CSR and earnings management using three independent variables — economic, environmental, and social dimensions of CSR — and two dependent variables: discretionary accruals and real activity-based earnings management. Control variables include firm size, leverage, and return on assets. A purposive sample of 65 listed companies, selected from 294 based on CSR disclosure according to the GRI index, provided data from annual reports spanning 2017-2023. Findings indicate that the economic dimension of CSR positively influences both discretionary accruals and real activity-based earnings management. Conversely, the environmental dimension shows a negative impact on these forms of earnings manipulation. The social dimension of CSR was found to have an insignificant effect on both dependent variables. The study suggests that companies focus on CSR initiatives that can be enhanced through stakeholder theory and highlights the importance of developing CSR standards tailored to Sri Lanka. Additionally, the research provides insights into detecting earnings management through various measurement models, contributing valuable knowledge to the Sri Lankan context.
Keywords: CSR; Discretionary accruals; Firm size; Real earning management